Government Public Communication Management Strategy in Socializing the People's School Policy in Indonesia - Novianty Elizabeth Ayuna (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
The People's School Policy—a free, boarding-based education program for low-income families. The success of this policy depends heavily on the effectiveness of information delivery, public acceptance, and community participation. This study aims to analyze the public communication management strategies implemented by the government in its outreach. This research uses a descriptive qualitative approach with a case study method. The results indicate that the government implemented a mixed-method communication strategy, combining direct face-to-face outreach (a community approach) and the use of digital media (social media/websites) for information transparency. The results indicate that the government implemented a single narrative strategy of "Education for All" to maintain information consistency across ministries (Ministry of Social Affairs, Ministry of Primary and Secondary Education, and Ministry of State Secretariat). The implementation strategy was carried out through multi-platform channels that combined social media for the wider public with face-to-face communication and the use of regional languages ​​for communities in remote areas. In addition, issue management through rapid responses through official complaint channels and strategic collaboration with universities were key factors in building public trust. This study concludes that the integration of digital channels and a local humanist approach is effective in expanding the reach of policies, although synchronizing technical data between the central and regional governments remains a managerial challenge that needs to be optimized to achieve the target of 500 schools by 2029.